Comparison of Sonography versus Digital Breast Tomosynthesis to Locate Intramammary Marker Clips - Schulz-Wendtland, R.; Dankerl, P.; Dilbat, G.; Bani, M.; Fasching, P. A.; Heusinger, K.; Lux, M. P.; Loehberg, C. R.; Jud, S. M.; Rauh, C.; Bayer, C. M.; Beckmann, M. W.; Wachter, D. L.; Uder, M.; Meier-Meitinger, M.; Brehm, B. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: This study aimed to compare the accuracy of sonography versus digital breast tomosynthesis to locate intramammary marker clips placed under ultrasound guidance. Patients and Methods: Fifty patients with suspicion of breast cancer (lesion diameter less than 2 cm [cT1]) had ultrasound-guided core needle biopsy with placement of a marker clip in the center of the tumor. Intramammary marker clips were subsequently located with both sonography and digital breast tomosynthesis. Results: Sonography detected no dislocation of intrammammary marker clips in 42 of 50 patients (84 %); dislocation was reported in 8 patients (16 %) with a maximum dislocation of 7 mm along the x-, y- or z-axis. Digital breast tomosynthesis showed accurate placement without dislocation of the intramammary marker clip in 48 patients (96 %); 2 patients (4 %) had a maximum clip dislocation of 3 mm along the x-, y- or z-axis (p < 0.05). Conclusion: The use of digital breast tomosynthesis could improve the accuracy when locating intramammary marker clips compared to sonography and could, in future, be used to complement or even completely replace sonography.
Keywords: intramammary clip marker system; ultrasound-guided core needle biopsy; digital breast tomosynthesis (DBT)